PEMBERDAYAAN MASYARAKAT MELALUI PROGRAM KELOMPOK TANI (STUDI KASUS DI KELOMPOK TANI TNAO MAT DESA MNELALETE KECAMATAN AMANUBAN BARAT KABUPATEN TIMOR TENGAH SELATAN) - Leppa, Joshua De Fatima; Syukur, Abdul; Makleat, Nirwaning; Neonufa, Samrid (Universitas Nusa Cendana, 2023)
Abundant natural resources cannot be utilized properly for the needs of the surrounding community, so learning efforts are needed to manage the potential of natural resources owned through empowering the community. The purpose of this research is to find out how Jim Ife's theory of community empowerment is applied to community empowerment programs through farmer groups. This study used a qualitative case study approach with the research subject being the head of the Farmers' Group, members of the Farmers' Group and Agricultural Extension Officers of the Farmer's Group. Data collection was carried out by interview and observation techniques. The results showed that the process of community empowerment through the Farmer Group program can be said to be quite good in terms of applying the community empowerment perspective according to Jim Ife, in the Tnao Mat farmer group there is a community empowerment program, namely meetings between field agricultural extension workers and members of farmer groups, where there is counseling, socialization and training on agriculture that helps farming communities manage their natural resources. The end result of the empowerment program is that members of farmer groups are able to independently improve their quality of life and no longer depend on community empowerment program activities being held, especially helping them find solutions/problem solving to the social problems they face.